Overview of Wireless Implantable Energy Supply and Communication Technology - Zhang, Shuang; Qin, Yuping; Kuang, Jiang-ming; Yang, Jining; Xu, Jin; Wang, Jiujiang; Liu, Yihe (Recent Patents on Engineering, 2021)
With the development of integrated circuits and microelectronics, integrated and miniaturized implantable medical devices are increasingly used in modern medical technologies, e.g., cardiac pacemakers, vasodilators, and cochlear implants. However, the normal operation of these devices is inseparable from the availability of sufficient energy supply and the bidirectional transmission of internal and external signals. Due to the limitation of the working environment of sensors, there is only a small space for most implanted electronic devices, which is a challenge faced by existing technology. In this paper, current wireless implantable energy supply and communication technologies are reviewed to determine the best available technologies, thereby providing a reference for method selection in designing implantable medical systems.
Keywords: Implantable medical devices